2008
DOI: 10.1080/01621420802022548
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Acceptability of Canadian Home and Community-Based Services: Perspectives of Family Caregivers of Persons with Dementia

Abstract: Thirty-five percent of Canadians over the age of 85 have dementia, and up to 90% of their home care is provided by family and friends. The purpose of this study was to explore the use and satisfaction with home and community-based services for persons with dementia from the perspectives of family caregivers. The study was conducted using an interpretive, descriptive, qualitative approach. Six focus groups (N = 36) and three personal interviews were conducted with rural and urban caregivers in Ontario, Manitoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 19 publications
(17 reference statements)
6
64
0
1
Order By: Relevance
“…Eighty percent of Canadians support the enhancement of home-and community-based care to broaden the overall health care system (Health Council of Canada, 2008). Research support does exist for team-based services (Health Council of Canada, 2008;Jansen, 2008) within an integrated community care system (Anderson & Parent, 2000;Forbes et al, 2008b). This study may inform planning and evaluation strategies to reorient the home care system; enhance nursing and interdisciplinary team care; and improve the quality, availability, and acceptability of home-and community-based dementia care.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Eighty percent of Canadians support the enhancement of home-and community-based care to broaden the overall health care system (Health Council of Canada, 2008). Research support does exist for team-based services (Health Council of Canada, 2008;Jansen, 2008) within an integrated community care system (Anderson & Parent, 2000;Forbes et al, 2008b). This study may inform planning and evaluation strategies to reorient the home care system; enhance nursing and interdisciplinary team care; and improve the quality, availability, and acceptability of home-and community-based dementia care.…”
Section: Discussionmentioning
confidence: 88%
“…The Council report revealed that one-quarter of Canadians cared for a family member or a close friend with a serious health issue in the last year, with 22% of these people absent from their place of employment for one or more months, and 41% using personal financial resources during the time of caregiving. Essential home care services are becoming less available through the publicly funded home care system, and greater proportions of those with dementia are turning to the private sector for assistance (Forbes et al, 2008b;Forbes et al, 2006). Those who do not have the financial resources to pay for private services may not receive any in-home assistance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations